Infection of two distinct Trichuris sp. genotypes within and among baboon (Papio ursinus) troops on the Cape Peninsula, South Africa - Moxley, Courtney (Department of Biological Sciences, 2014)
The chacma baboon (Papio ursinus) population on the Cape Peninsula, South Africa is divided into 16 geographically isolated troops, 14 of which are classified as being commensal with humans. Regular contact with humans in urban and agricultural settings may have increased the risk of transmission of the different parasite species identified within this population. The aim of the study was to identify whether two previously-identified genotypes of the whipworm, Trichuris sp., infect the same individual baboon simultaneously and whether both genotypes infect baboons of different troops on the Peninsula. Genomic DNA was extracted from adult Trichuris worms extracted from the gastrointestinal tract of six baboons from five different troops on the Peninsula. Two sets of primers were designed to amplify different sized products of the ITS1-5.8S-ITS2 region of the ribosomal DNA through PCR. Diagnostic PCR revealed the DG genotype among two Trichuris sp. specimens in a baboon from an unknown troop, while the CP-GOB genotype was observed among five specimens within a baboon from the Groot Olifantsbos troop. Sequence data confirmed the presence of a single genotype in each troop. This study suggests that the genotypes are specific to baboon troops but the potential for both genotypes to infect baboons within troops on the Peninsula cannot be ruled out. Knowledge of the specificity of the Trichuris genotypes to baboon hosts of different troops may inform our understanding of the evolution of diversity within this genus. Future research into the transmission of both genotypes within and between troops may also highlight the potential for two distinct species of Trichuris to exist among the baboons. Considering the close contact between baboons and humans on the Peninsula, clarification on host specificity of either genotype will also be important for managing zoonoses and preventing break-outs of infectious diseases between the species.